Concurrent Chemoradiotherapy in the Adjuvant Treatment of High-risk Primary Salivary Gland Malignancies - Gebhardt, Brian J. (Am J Clin Oncol, 2018)
OBJECTIVES: Adjuvant radiation therapy (RT) is indicated for patients with salivary gland malignancies with risk factors for recurrence following resection. We analyzed patients treated with adjuvant RT with or without concurrent chemotherapy to determine the impact of prognostic and treatment factors. MATERIALS AND METHODS: Retrospective analysis was performed of 128 patients treated with surgical resection followed by intensity-modulated radiotherapy. In total, 31 (24.2%) patients were treated with concurrent chemoradiotherapy. The Kaplan-Meier method was used to estimate rates of progression-free survival (PFS), local-regional control, distant control, overall survival. Multivariable Cox regression was performed to evaluate factors significant on univariate analysis. RESULTS: The 5-year rates of PFS, local-regional control, freedom-from distant metastasis, and overall survival were 61.2%, 85.8%, 76.5%, and 73.7%, respectively. Predictors of decreased PFS on univariate analyses were age, tumor stage, nodal stage, positive surgical margins, histology, high grade, perineural invasion, lymphovascular space invasion, extranodal extension, and use of chemoradiotherapy. On multivariable analysis, elevated T-stage, positive surgical margins, and presence of extranodal extension were predictive of decreased PFS. The acute toxicity rates were 30.3% grade 1, 51.5% grade 2, 11.4% grade 3, and 0.8% grade 4. There was no difference in rates of grade 3 or higher acute toxicity with use of RT alone versus chemoradiotherapy (P = 0.183). CONCLUSIONS: Use of chemoradiotherapy for adjuvant treatment of salivary gland malignancies was well-tolerated, but no improvement in survival was seen with the use of chemoradiotherapy in both the overall study population and a subset with high-risk features. Caution should be used when using this modality until randomized evidence becomes available.